Directions for transformation of financial products and services in the context of the pandemic - E. I. Kulikova (Путеводитель предпринимателя)
While investigating the external factors that influenced the development of the economy in 2020 and analyzing the negative consequences of the declared COVID–19 pandemic, the author also identifies positive changes in the innovation sphere of companies in terms of the development of new products, technologies and management mechanisms.